2020
DOI: 10.1126/sciadv.aaz5746
|View full text |Cite
|
Sign up to set email alerts
|

Postweaning maternal care increases male chimpanzee reproductive success

Abstract: Humans are unusual among animals for continuing to provision and care for their offspring until adulthood. This “prolonged dependency” is considered key for the evolution of other notable human traits, such as large brains, complex societies, and extended postreproductive lifespans. Prolonged dependency must therefore have evolved under conditions in which reproductive success is gained with parental investment and diminished with early parental loss. We tested this idea using data from wild chimpanzees, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 69 publications
(111 reference statements)
0
37
0
Order By: Relevance
“…This is not the case for male offspring. Mother–son cohabitation during reproductive ages of sons has the potential to improve the reproductive success of sons, for instance in bonobos 54 and in this population of chimpanzees 55 . Here, we showed that females with sons approaching reproductive age in the community were more likely to participate in intergroup encounters in comparison to females with no such sons in the community.…”
Section: Discussionmentioning
confidence: 99%
“…This is not the case for male offspring. Mother–son cohabitation during reproductive ages of sons has the potential to improve the reproductive success of sons, for instance in bonobos 54 and in this population of chimpanzees 55 . Here, we showed that females with sons approaching reproductive age in the community were more likely to participate in intergroup encounters in comparison to females with no such sons in the community.…”
Section: Discussionmentioning
confidence: 99%
“…Physical, cognitive, emotional, and social development can be impaired as well in both bonobos and chimpanzees 40 , 45 – 48 . Even after weaning, the loss of a mother negatively affects males’ reproductive success 49 , 50 . Only one case of adoption has been reported in wild bonobos: a 4 year old male infant was adopted by his older brother after their mother’s death and survived for > 2 years 51 .…”
Section: Introductionmentioning
confidence: 99%
“…While the effect of maternal loss on wild animal survival and reproduction has been recently established ( Foster et al, 2012 ; Andres et al, 2013 ; Tung et al, 2016 ; Walker et al, 2018 ; Surbeck et al, 2019 ; Crockford et al, 2020 ; Zipple et al, 2021 ), the mechanisms underlying these fitness costs remain understudied. Our study provides one of the rare empirical tests of the BEM (see also Rosenbaum et al, 2020 ) and ACM in wild long-lived mammals by assessing the short- and long-term physiological impacts of early maternal loss.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, mothers are essential for the early development of their infants since they provide postnatal care ( Maestripieri and Mateo, 2009 ). Maternal loss in mammals reduces growth ( Samuni et al, 2020 ), survival ( Watts et al, 2009 ; Andres et al, 2013 ; Tung et al, 2016 ; Stanton et al, 2020 ), and long-term reproductive success ( Andres et al, 2013 ; Strauss et al, 2020 ; Crockford et al, 2020 ; Zipple et al, 2021 , reviewed in Clutton-Brock, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation